Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 1994
DOI: 10.1145/191666.191759
|View full text |Cite
|
Sign up to set email alerts
|

User learning and performance with marking menus

Abstract: A marking menu is designed to allow a user to perform a menu selection by either popping-up a radial (or pie) menu, or by making a straight mark in the direction of the desired menu item without popping-up the menu. Previous evaluations in laboratory settings have shown the potential of marking menus. This paper reports on a case study of user behavior with marking menus in a real work situation. The study demonstrates the following: First, marking menus are used as designed.When users become expert with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(102 citation statements)
references
References 13 publications
0
91
0
11
Order By: Relevance
“…They find the technique easy to learn, complementing standard techniques that they already know how to use. This suggests that the transient techniques are approachable for novice to intermediate users, and may serve as an easy transition to expert use [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They find the technique easy to learn, complementing standard techniques that they already know how to use. This suggests that the transient techniques are approachable for novice to intermediate users, and may serve as an easy transition to expert use [11].…”
Section: Discussionmentioning
confidence: 99%
“…transient pan should resemble standard pan) to facilitate a transition to expert-level behaviour through rehearsal of familiar, novice gestures [11].…”
Section: Designing Transient Pan-and-zoommentioning
confidence: 99%
“…This blossom help (described in Figure 7) also functions as a mechanism to support goal navigation and exploration. This help approach is an elaboration on the marking menu reported by Kurtenbach & Buxton [1994]. To improve the usability a function can be activated using the correct gesture or using a text label as a buttons.…”
Section: Rewindmentioning
confidence: 99%
“…Gestures were incorporated using simple gradient strokes to select a letter and simple meaningful gestures to access other functions, such as numbers and uppercase letters. To operate the keyboard (see Figure 10) the user makes very simple gradient gestures, as described by Kurtenbach & Buxton [1994]. To select a letter, a gradient stroke that starts over the selected button is performed.…”
Section: Proposed Solutionmentioning
confidence: 99%
“…Prior studies showed that feedback can provide users with a better understanding of the system, facilitating a swift transition from novice to expert [14]. Yet most current tangibles are passive and do not provide any feedback on tangible interactions [22].…”
Section: Introductionmentioning
confidence: 99%